Comparison of Drill Method and Game Method Long Jump Training in An Effort to Improve Students' Long Jump Abilities - Iskandar, Iskandar (JOURNAL RESPECS (Research Physical Education and Sports), 2024)
This research is experimental research which aims to determine the comparison of drill training methods and game training methods in improving students' abilities in the long jump. The research design used was Two Group Pre-test and Post-test. The sample used was 50 students from the Education, Physical, Health and Recreation Study Program at FIK UNM, divided into 2 groups. The sample was determined using a purposive sampling technique, by establishing certain criteria. To answer the hypothesis in this research, a t-test was carried out. Based on the results of data analysis, it is known that the Sig. (2-tailed) is 0.003 < 0.05, which means that there is a significant difference in the average value between the drill training method and the game training method. Where the mean value of the drill training method is 472.12 or greater than the mean value of the game training method of 441.28 with the difference between the two mean values being 30.84. So, based on this explanation, it can be concluded that the drill training method is better than the game training method in improving the long jump ability of students in the Education, Physical, Health and Recreation Study Program at FIK UNM.